Active site alanine mutations convert deubiquitinases into high‐affinity ubiquitin‐binding proteins. (27th August 2018) - Morrow, Marie E; Morgan, Michael T; Clerici, Marcello; Growkova, Katerina; Yan, Ming; Komander, David; Sixma, Titia K; Simicek, Michal; Wolberger, Cynthia
Abstract: A common strategy for exploring the biological roles of deubiquitinating enzymes (DUBs) in different pathways is to study the effects of replacing the wild‐type DUB with a catalytically inactive mutant in cells. We report here that a commonly studied DUB mutation, in which the catalytic cysteine is replaced with alanine, can dramatically increase the affinity of some DUBs for ubiquitin. Overexpression of these tight‐binding mutants thus has the potential to sequester cellular pools of monoubiquitin and ubiquitin chains. As a result, cells expressing these mutants may display unpredictable dominant negative physiological effects that are not related to loss of DUB activity. The structure of the SAGA DUB module bound to free ubiquitin reveals the structural basis for the 30‐fold higher affinity of Ubp8 C146A for ubiquitin. We show that an alternative option, substituting the active site cysteine with arginine, can inactivate DUBs while also decreasing the affinity for ubiquitin. Synopsis: Mutation of deubiquitinating enzyme (DUB) active site cysteine to alanine dramatically increases the affinity of some DUBs for mono‐ and polyubiquitin chains. Expression of these alanine mutant DUBs in cells could therefore give rise to spurious or dominant negative effects due to the potential of these DUBs to protect polyubiquitin from cleavage and sequester ubiquitin. Mutation of DUB active site cysteines to alanine relieves steric hindrance, which allows tighter binding of ubiquitin's C‐terminus. In vitro, C‐to‐A mutations lead to a 10–150‐fold increase in binding affinity of DUBs for monoubiquitin or polyubiquitin. In cells, overexpressed C‐to‐A mutant DUBs act as high affinity ubiquitin binding domains, thereby sequestering ubiquitinated proteins from deubiquitination, which leads to a dramatic accumulation of polyubiquitin and ubiquitinated substrates. We recommend the use of arginine active site mutations to avoid undesired dominant negative effects in cellular studies of inactive DUBs. Abstract : Mutation of the active site cysteine to alanine dramatically increases the affinity of some deubiquitinases (DUBs) for ubiquitin, potentially giving rise to spurious or dominant negative effects due to their potential to sequester ubiquitin and to protect ubiquitinated substrates.